THERMAL COMFORT IN TECHNICAL SCHOOL: PHYSICAL MEASUREMENT APPROACH - N. K., Makhtar; A. R. , Ismail; N. , Jusoh; A. P. , Puvanasvaran (2010)
A field study on the relationship between thermal comfort and students’ performance was carried out in a technical school in Selangor. The buildings were mechanically ventilated by fans. The measured environmental parameters were air temperature (ºC), mean radiant temperature (ºC), relative humidity (%) and air velocity (m/s) of the surrounding classroom area. The environmental factors were measured using Thermal Comfort Equipment, which is capable to measure simultaneously all the environmental factors. All the windows were left open for natural ventilation. Subjective measurements were also conducted using survey questionnaire on the same days when the environmental factors were measured. The Predicted Mean Vote (PMV) was calculated using ASHRAE Thermal sensation scale which has been proposed earlier by Fanger (1970) for the measured data. Further Predicted Percentage Dissatisfied (PPD) was used to estimate the thermal comfort satisfaction of the occupant. The study revealed that 70% of the students’ population at the classroom is dissatisfied with the thermal comfort.